Effect of Structured Training Workshop on Nurses’ Drug Dosage Calculation Competence at Tertiary Care Hospitals of Faisalabad - Mehreen Komal, Hafiza Saba Javed, Namra (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Drug administration is a major component of patient care provided by nurses at hospitals. Appropriate drug administration ensures patient safety, as incorrect or unsafe administration can result in adverse patient health and hospital outcomes. Drug dosage calculation errors are the most common, threatening patient safety, lengthening patients’ hospital stay and increasing associated costs worldwide. Aim: To evaluate the effectiveness of structured training workshop at enhancing nurses’ competence in drug dosage calculations. Methods: One group pre-test post-test quasi-experimental study was conducted on a convenient sample of 73 staff nurses working at public tertiary care hospitals of Faisalabad, Pakistan. Staff nurses aged 21-60 years who provide direct patient care, were included in the study.The study duration spanned over 04 months from July to October 2020. A structured questionnaire was used for the pre-test and post-test competency level of nurses in drug dosage calculations. The study intervention consisted of a structured training workshop focusing on basic mathematical skills for drug dosage calculation using the correct mathematical formula for unit conversions and linking the correct dose to the patient case scenario. SPSS version 26 was used for with-in group analysis employing t-test statistics. Results: Pre-test results revealed common errors in the application of basic mathematical principles for drug concentration unit conversions and complex calculations involving patient-age, weight and other variables.Post-test results demonstrated a significant improvement in level of competence of participant nurses in this regard, indicated by significant difference (p-value 0.000). Structured training workshop was found effective in enhancing nurses’ competency level in drug dosage calculations. Practical implication Conclusion: Structured training improved nurses’ ability to identify drug calculation errors, understand the use of the correct formula, and calculate drug dosage accurately. This study emphasizes the importance of structured education and training of nurses aimed at reducing medication errors and improving patient health and hospital outcomes. Keywords: Competence; Drug dosage calculation; Nurses; Quasi experimental study; Pakistan; Workshop.